THE EFFECTIVENESS OF EVERY ONE IS TEACHER HERE (ETH) TYPE ACTIVE LEARNING STRATEGY ON LEARNING OUTCOMES OF CLASS II STUDENTS IN JUNIOR HIGH SCHOOLS PRIVATE MUHAMMADIYAH AT TAQWA TEBING TINGGI - Winda Novianti; Ine Ismayanti Purba (RADJA PUBLIKA, 2022)
The current research study utilizes a type of correlation research, meaning that it is related or interrelated. That is, there is a reciprocal relationship between one variable and another variable. The results of this study are based on the results of calculations with the help of IBM SPSS 22 for windows software, it can be seen that of the 12 statements tested it can be seen that all instruments are valid, becausethe results of rcount > rtable. Meanwhile, based on Cronbach's alpha value of 0.972, it can be obtained that the questionnaire is declared reliable. Based on data analysis it is known that the relationship obtained through the product moment correlation test between active learning strategies of the Every One Is Teacher Here (ETH) type and learning outcomes in Muhammadiyah Private Middle Schools At Taqwa Tebing Tinggi of 0.630. These results are interpreted roughly or simply by matching the calculation results with the correlation index number